Identification of a 5-Methylcytosine Site (mC-7) That May Inhibit CXCL11 Expression and Regulate E. coli F18 Susceptibility in IPEC-J2 Cells - Xiaoru Shi; Luchen Yu; Rufeng Huang; Wenbin Bao; Shenglong Wu; Zhengchang Wu (Veterinary Sciences, 2022)
The primary pathogen causing post-weaning diarrhea in piglets is Escherichia coli F18 (E. coli F18), hence it is essential to investigate the mechanism governing E. coli F18 resistance in native pig breeds. Based on the previous RNA-seq results of the duodenum from E. coli F18-resistant and -susceptible Meishan piglets, CXCL11, an important functional gene, was preliminarily screened. In this investigation, in order to further examine the expression regulation mechanism of E. coli F18 in intestinal porcine epithelial cells (IPEC-J2) against E. coli F18 infection, CXCL11 gene expression on IPEC-J2 cells infected by E. coli F18 was detected, which was significantly downregulated (p < 0.01). Secondly, the overexpression on the IPEC-J2 cell line was successfully structured, and a relative quantification method of the PILIN, bacteria enumeration, and immunofluorescence assay indicated that the CXCL11 overexpression significantly reduced the ability of E. coli F18 to interact with IPEC-J2 in vitro. The promoter region of the CXCL11 gene was predicted to contain a CpG island (−619 ~ −380 bp) of which 13 CpG sites in the sequencing region were methylated to varying degrees, and the methylation level of one CPG site (mC-7) positively linked negatively with the expression of the CXCL11 gene (p < 0.05). Meanwhile, a dual luciferase assay detected the mutation of the mC-7 site that significantly inhibited the luciferase activity of the CXCL11 gene promoter (p < 0.01). Transcription factor prediction and expression verification indicated that mC-7 is located in the OSR1-binding domain, and that its expression level is related to E. coli F18 susceptibility. We speculated that methylation modification of the mC-7 site of the CpG island in the promoter region of the CXCL11 gene might inhibit the binding of transcription factor OSR1 with the mC-7 site, and then affect its expression level to regulate the susceptibility to E. coli F18.